2011
DOI: 10.12681/mms.39
|View full text |Cite
|
Sign up to set email alerts
|

Is natural bait type a stochastic process for size and condition of fishes in the recreational fishery of Ιzmir Bay?

Abstract: Determining bait type might be one of the most important factors that influence the amount and size of the fish catch in marine recreational fishery. To this end, the relationships between two types of natural bait and catch per unit effort (CPUE), yield per unit effort (YPUE), fish size and condition (K=W/TL 3 *100) were evaluated in the recreational fishery of zmir Bay (Middle Eastern Aegean Sea, Turkey). The most abundant angling species on Turkish coasts: annular sea bream (Diplodus annularis), blotched pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 9 publications
0
12
0
5
Order By: Relevance
“…The CPUE and YPUE values, calculated with the formula recommended by Godøy et al (2003) and customized by Aydın (2011), are presented below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CPUE and YPUE values, calculated with the formula recommended by Godøy et al (2003) and customized by Aydın (2011), are presented below.…”
Section: Methodsmentioning
confidence: 99%
“…The Kolmogorov-Smirnov (K-S) test was used to determine differences between size frequency distributions of fish caught by hooks of varying sizes (Siegel and Castellan, 1989;Karakulak and Erk, 2008;Aydın, 2011).…”
Section: W= Weight (G)mentioning
confidence: 99%
“…Smith () detected a relationship between the type of natural bait (either maggots or chironomids) and the vulnerability of the fish. Aydin () compared sardine ( Sardina pilchardus , Clupeidae) and onyx ( Solen vagina , Solenidae) in a Turkish recreational fishery and found that onyx captured considerably more fish than sardine; however, individuals with higher condition factors were more frequently captured using sardine. Similarly, Alós, Arlinghaus et al () found that the Mediterranean fishes were more vulnerable to worms than to shrimp, suggesting that the proper selection of bait by the fisher can move fish from an invulnerable to a vulnerable state.…”
Section: Review Of Factors Underlying Fish Vulnerabilitymentioning
confidence: 99%
“…The economic and ecological impacts of RF were previously presented in few studies from the Mediterranean SEA (LLORET et al, 2008;ÜNAL et al, 2010;AYDIN, 2011;FONT AND LLORET, 2011a;FONT & LLORET, 2011b;TUNCA et al, 2012;AYDIN et al, 2013;TUNCA et al, 2016). Despite of the fact that RF has important economic and ecological consequences, there is lack of its management besides commercial fishing with high numbers of illegal, unreported and unregulated recreational fishing (GORDOA et al, 2004;LLORET et al, 2008;ÜNAL et al, 2010).…”
Section: Introductionmentioning
confidence: 85%